Strength of Bamboo (Dendrocalamus strictus) - Limay, V. D. (Indian Forester, 1952)
Bamboo has recently attracted considerable attention for use as a constructional material. It grows quickly and can be produced as a short rotational forest crop. Its supply can, therefore, be practically unlimited. It is very common all over India. It is cheap and above all it is very strong. Engineers have been thinking of using it in place of steel for reinforcement of cement concrete construction and enquiries are often being received at the Forest Research Institute for reliable strength data on bamboo. In view of the growing interest in the strength of bamboo, tests on scientific lines were undertaken by the Timber Mechanics Branch to investigate the influence of seasoning, age, position of the node and position along the culm, etc., on the strength of the bamboo specimens. To begin with, tests were done on Indian bamboo of the species of Dendrocalamus strictus which is the most common bamboo in India. Material for tests tor this experiment was obtained from the New Forest area and a factorial experiment was laid out including the following variants in the four different factors, namely (A) Seasoning - 2 groups, ( B ) Age- 4 different ages, ( C) Disposition of nodes - 2 positions and (D) Position along culm - 3 positions. There were altogether 48 factorial combinations for each of the two strength properties studied, namely, static bending and compression parallel to grain. The total number of specimens tested was about 1,000. The results of tests were statistically analysed and strength figures as finally determined have been given in Table 10 together with similar strength figures for other bamboos tested earlier. This publication thus fulfils a great need and places in the hands of engineers strength data that is available at present. The help of Dr. K. R. Nair, Statistician, Forest Research Institute, and his staff in analysing the data is gratefully acknowledged.